Modeling of COMPASS tokamak divertor liquid metal experiments. (December 2020) - Horacek, J.; Dejarnac, R.; Cecrdle, J.; Tskhakaya, D.; Vertkov, A.; Cavalier, J.; Vondracek, P.; Jerab, M.; Barton, P.; van Oost, G.; Hron, M.; Weinzettl, V.; et al.
Abstract: Two small liquid metal targets based on the capillary porous structure were exposed to the divertor plasma of the tokamak COMPASS. The first target was wetted by pure lithium and the second one by a lithium-tin alloy, both releasing mainly lithium atoms (sputtering and evaporation) when exposed to plasma. Due to poorly conductive target material and steep surface inclination (implying the surface-perpendicular plasma heat flux 12–17 MW/m 2 ) for 0.1–0.2 s, the LiSn target has reached 900 °C under ELMy H-mode. A model of heat conduction is developed and serves to evaluate the lithium sputtering and evaporation and, thus, the surface cooling by the released lithium and consequent radiative shielding. In these conditions, cooling of the surface by the latent heat of vapor did not exceed 1 MW/m 2 . About 10 19 lithium atoms were evaporated (comparable to the COMPASS 1 m 3 plasma deuterium content), local Li pressure exceeded the deuterium plasma pressure. Since the radiating Li vapor cloud spreads over a sphere much larger than the hot spot, its cooling effect is negligible (0.2 MW/m 2 ). We also predict zero lithium prompt redeposition, consistent with our observation.